Four arenas: Malaysia's 2018 election, reform, and democratization. Issue 4 (18th May 2020) - Ostwald, Kai; Oliver, Steven
ABSTRACT: Malaysia's 2018 election ended more than six decades of dominant party rule by the United Malays National Organisation (UMNO). Three questions are paramount. How did the opposition finally achieve victory? What did voters who rejected UMNO actually vote for ? Finally, what do the answers imply for reform and democratization? We argue that Malaysia is comprised of four distinct identity-based polities, each with a unique electoral dynamic and vision for the country's political future. Using this framework provides valuable insights into UMNO's defeat, which was achieved by making inroads, largely through elite splits, into two arenas that were previously impenetrable for the opposition. One arena remains electorally pivotal and thus exerts a disproportionately large influence on the new government's reform agenda, entrenching the primacy of identity politics and ensuring the continuity of many policies that address ethnic relations. The case illustrates the extensive impact of divided polities and regionalism on democratization.